Ecology and evolution of facilitation among symbionts. Issue 1 (December 2018) - Zélé, Flore; Magalhães, Sara; Kéfi, Sonia; Duncan, Alison
Abstract Facilitation occurs when one species positively impacts the fitness of another, and has predominantly been studied in free-living species like plants. Facilitation can also occur among symbiont (mutualistic or parasitic) species or strains, but equivalent studies are scarce. To advance an integrated view of the effect of facilitation on symbiont ecology and evolution, we review empirical evidence and their underlying mechanisms, explore the factors favouring its emergence, and discuss its consequences for virulence and transmission. We argue that the facilitation concept can improve understanding of the evolutionary forces shaping symbiont communities and their effects on hosts. Facilitation is a well-known ecological interaction among free-living species, but symbionts residing in or on a host can also positively affect other symbiont species. Here, the authors review examples of facilitation among symbionts, revealing how facilitation theory can improve understanding of these interactions.